1997
DOI: 10.1046/j.1365-2648.1997.1997025634.x
|View full text |Cite
|
Sign up to set email alerts
|

From nurse to teacher: recognizing a status passage

Abstract: The purpose of this study is to examine the career trajectories of nurse teachers. The main focus of the study is the process of transition from nurse to teacher. The study looks at the anticipations, expectations, contrasts and changes encountered by nurse teachers when first embarking on the role. The interest lay in obtaining the teachers' view of their career trajectories and their experience of status transition. An ethnographic approach was adopted, and in-depth interviews were carried out with nurse tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 10 publications
1
21
0
2
Order By: Relevance
“…The lecturers appear to find their transition to higher education confusing and challenging partly because of these tensions within their workplace over what a lecturer in teacher or nurse education should be. This confusion is in line with previous findings on lecturers in nursing (MacNeil, 1997;McArthur-Rouse, 2007).…”
Section: Workplace Tensionssupporting
confidence: 90%
See 1 more Smart Citation
“…The lecturers appear to find their transition to higher education confusing and challenging partly because of these tensions within their workplace over what a lecturer in teacher or nurse education should be. This confusion is in line with previous findings on lecturers in nursing (MacNeil, 1997;McArthur-Rouse, 2007).…”
Section: Workplace Tensionssupporting
confidence: 90%
“…This study found that 'lack of understanding about the functioning of the organization' was a considerable challenge for the new nurse educators and that they were unsure about their role. In a previous study (MacNeil, 1997), many of the interviewees had been lecturers in nursing for a 'considerable length of time' and the study identified a 'troublesome duality' which was seen to cause role ambiguity for the lecturers; they were trying to be a nursing practitioner as well as a lecturer.…”
Section: Workplace Learning In Academic Contextsmentioning
confidence: 99%
“…This study found that 'lack of understanding about the functioning of the organization' was a considerable challenge for the new nurse educators and that they were unsure about their role. In a previous study (MacNeil, 1997), many of the interviewees had been lecturers in nursing for a 'considerable length of time' and the study identified 'lack of affirmation' as an element of the experience of the lecturers; they did not gain the same level of feedback from students as they had received in their practitioner roles from patients and their relatives. The study also identified a 'troublesome duality' which was seen to cause role ambiguity for the lecturers; they were trying to be a nursing practitioner as well as a lecturer.…”
Section: The Literature: Workplace Learning In Academic Contextsmentioning
confidence: 94%
“…Samal ajal võivad praktikud õpetamisel tajuda vastuolusid neile kõrg-koolide poolt ja kutsetöös esitatavate ootuste vahel (MacNeil, 1997;Smith & Boyd, 2012). Vastuolud võivad tekkida olukorras, kus kõrgkooli õppejõuna tööle asunud praktikutelt ei eeldata üksnes töökogemuse jagamist, vaid ka nt õpetamisoskusi ning eriti oskust teooriat ja praktikat seostada.…”
Section: Praktik-õppejõud Kui Kutseala Esindaja Rakenduskõrgkoolisunclassified
“…Vastuolusid võivad praktikud tunnetada, kui ootused neile kui õppe-jõududele on teised võrreldes ootustega kutsetöös (nt MacNeil, 1997;Smith & Boyd, 2012). Näiteks võivad praktikud-õppejõud tajuda vastuolu olukorras, kus kõrgkool ootab neilt õpetamisoskusi, praktikud ise aga lähtu-vad kogemuste jagamise vajadusest.…”
Section: Aruteluunclassified